2010
DOI: 10.14234/elehe.v2i1.14
|View full text |Cite
|
Sign up to set email alerts
|

How might inclusive approaches to assessment enhance student learning in HE?

Abstract: This article reports some of the results from an investigation into issues around inclusivity in assessment undertaken at the University of Northampton (2009Northampton ( -2010. The Assess4success research project was conducted within a framework provided by the Higher Education Academy Summit programme on inclusive learning and teaching, and sought to explore the extent to which inclusivity, (a high level commitment in the university"s access and teaching policies), was embedded in students" experiences of as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Likewise, there is still a great demand for holistic systems to be established for the improvement of assessment practices and the support of students completing assessments. Along these lines, recent scholarship reiterates the value of introducing flexibility in assessment practices (Kumar & Wideman, 2014;Lombardi, Murray, & Gerdes, 2011), perhaps by providing the option of a range of alternative assessments scaffolded by early formative work and timely feedback (Butcher, Sedgwick, Lazard, & Hey, 2010). This emphasis on flexibility and on students working with faculty to shape their distinctive assessment paths also underscores the important role of students as partners in inclusive learning communities.…”
Section: Inclusive Assessmentmentioning
confidence: 99%
“…Likewise, there is still a great demand for holistic systems to be established for the improvement of assessment practices and the support of students completing assessments. Along these lines, recent scholarship reiterates the value of introducing flexibility in assessment practices (Kumar & Wideman, 2014;Lombardi, Murray, & Gerdes, 2011), perhaps by providing the option of a range of alternative assessments scaffolded by early formative work and timely feedback (Butcher, Sedgwick, Lazard, & Hey, 2010). This emphasis on flexibility and on students working with faculty to shape their distinctive assessment paths also underscores the important role of students as partners in inclusive learning communities.…”
Section: Inclusive Assessmentmentioning
confidence: 99%
“…Similarly, we conclude that the adjustments to the teaching and evaluation methods are fundamental for faculty members to carry out inclusive practices. They recognise that, in some cases, without these adjustments, some students cannot learn and pass the subject successfully, as has been stated by students themselves in numerous occasions (Butcher et al, 2010;Wilson et al, 2014). Adjustments to the ways of communicating or allowing students to record the lectures contribute to a better understanding of the information by some disabled students (Moriña et al, 2015).…”
Section: Con Clus I On S and Discussionmentioning
confidence: 97%
“…Nevertheless, the most relevant difficulties that disabled students encounter in the university context include those found in the classrooms (Madaus et al, 2003). The lack of adjustments in teaching methodologies, educational resources and the evaluation systems is a barrier that hinders, to a great extent, the learning of disabled students (Butcher et al, 2010). Despite the fact that a large number of universities contemplate these adjustments in their regulations as mandatory (Savvidou, 2011), in reality these actions usually depend on the good will and personal concern of faculty members (Gunersel & Etienne, 2014;Stes & Van Petegem, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4. Fourth, a study of inclusive language in assessment (Butcher et al, 2010) suggests a positive benefit to students from WP backgrounds. Inclusive language should be promoted to counter the 'uncommonsense' language of academic assessment (Donohue & Coffin, 2014), particularly when students are reported to adhere to a common sense understanding of the verbs used in assessment tasks (Williams, 2005).…”
Section: Literaturementioning
confidence: 99%
“…The research reported here took a more critical starting point -that aspects of the pedagogic environment itself were an unnecessary obstacle for WP students. Our hypothesis was that a smarter approach to retention, one which sought to intervene to change institutional culture, rather than fit square pegs into a round hole (Butcher et al, 2010), might offer a more inclusive and holistic solution.…”
Section: Introductionmentioning
confidence: 99%